Cloud point extraction-slotted quartz tube with four-exit holes-flame atomic absorption spectrometry combination for the determination of cobalt at trace levels in fennel tea samples after complexation with a Schiff base ligand - ozcan, Rumeysa; Kasa, Nursu Aylin; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (SPRINGER, 2021)
In this work, a cloud point extraction (CPE) method was optimized for the extraction and preconcentration of cobalt for trace determination by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS). A hydrophobic ion-associated cobalt complex was formed with a lab-made Schiff base ligand, synthesized from the reaction of 1-naphthylamine and 5-bromosalicylaldehyde. A univariate optimization was carried out for the main experimental parameters affecting the extraction efficiency. Under the optimum experimental conditions, the respective limits of detection and quantification were found to be 2.7 mu g L-1 and 8.9 mu g L-1 for cobalt. Approximately 65 folds enhancement in detection power was recorded for the analyte with respect to the traditional FAAS system. Both applicability and accuracy of the method were validated with spiking experiments performed in fennel tea samples at different concentrations (40, 50 and 75 mu g L-1). The percent recovery results were found in the range of 90-107%, establishing high accuracy and applicability to real samples.
Keywords: Cloud point extraction; Cobalt; Flame atomic absorption spectrometry; Fennel tea; Slotted quartz tube; LIQUID-LIQUID MICROEXTRACTION; WATER SAMPLES; ICP-OES; PRECONCENTRATION; NICKEL; COPPER; IONS; METALS; LEAD; FOOD; Food Science & Technology